Penerapan Red Flags Analysis dalam Mendeteksi Potensi Financial Statement Fraud di Pasar Modal Indonesia - Juliana Tannaka; Erica Stevanie; Olivia Olivia (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2025)
This study aims to describe the application of Red Flags Analysis in detecting potential financial statement fraud in the Indonesian capital market, using a descriptive qualitative approach through a literature review from various secondary sources. The results show that Red Flags Analysis is effective in identifying various fraud indicators, such as financial statement anomalies, delayed report publication, doubtful audit opinions, and consistent deviation patterns observed among publicly listed companies in Indonesia. The findings also emphasize the critical role of collaboration among auditors, regulators, and company management in building a proactive and ethical oversight system. The comprehensive application of this method significantly contributes to strengthening transparency, enhancing accountability, protecting investors from fraud risks, and ultimately improving the quality of the national capital market.